2019
DOI: 10.1136/ijgc-2019-000665
|View full text |Cite
|
Sign up to set email alerts
|

Integrated pre-surgical diagnostic algorithm to define extent of disease in cervical cancer

Abstract: ObjectivesSurvival of patients with cervical cancer is strongly associated with the local extent of the primary disease. The aim of the study was to develop an integrated diagnostic algorithm, including ultrasonography (USG), magnetic resonance imaging (MRI), and examination under anesthesia, to define the local extent of disease in patients with newly diagnosed cervical cancer.MethodsPatients with biopsy proven cervical cancer who underwent primary surgery from January 2013 to December 2018 in four participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Nevertheless, we found that VGS was more sensitive than MRI in excluding fornix infiltration, with an NPV of 100% and 88.9%, respectively. Recently, similar results have been reported by comparing the accuracy of histology to TVUS, MRI, and clinical examination under anesthesia [ 21 ]. TVUS can be a good method to exclude but not to predict vaginal infiltration, which is often overestimated.…”
Section: Discussionsupporting
confidence: 75%
“…Nevertheless, we found that VGS was more sensitive than MRI in excluding fornix infiltration, with an NPV of 100% and 88.9%, respectively. Recently, similar results have been reported by comparing the accuracy of histology to TVUS, MRI, and clinical examination under anesthesia [ 21 ]. TVUS can be a good method to exclude but not to predict vaginal infiltration, which is often overestimated.…”
Section: Discussionsupporting
confidence: 75%
“…However, the integrated pre-surgical diagnostic algorithm could better define the local extent of cervical cancer. 19 In our study, color Doppler flow signals were found in the cancerous tissue of all patients compared with normal cervical tissue, in which no detectable vascularization was found. The coincidence rate between pre-operative ultrasonography and tumor, nodes, and metastases staging was 87% in rare-type cervical cancer, which was higher than that reported by Byun et al (62.5%) but consistent with the rate reported by Ghi et al (85.7%).…”
Section: Discussionmentioning
confidence: 42%
“…Epstein et al showed a higher accuracy for ultrasonography compared to MRI in defining tumor size, especially for the tumors >4 cm(22). Sozzi et al showed a better diagnostic performance of ultrasonography compared to MRI and examination under anesthesia, especially for tumors >2 cm(14). In our opinion, combinatorial approaches with examination under anesthesia, ultrasonography, MRI, or PET/CT have important value in determining the tumor size.…”
mentioning
confidence: 78%